Giant Dilatation of the Right Coronary Aortic Bulb with Compression of the Right Ventricular Outflow Tract Mimicking a Ventricular Septal Defect: Diagnostic workup Using Echocardiography, Heart Catheterization, and Cardiac Computed Tomography. (16th August 2012) - Hofmann, Nina P.; Abdel-Aty, Hassan; Siebert, Stefan; Katus, Hugo A.; Korosoglou, Grigorios
Abstract : Annuloaortic ectasia is a relatively rare diagnosis. Herein, we report an unusual case of an annuloaortic ectasia with asymmetric dilatation of the right coronary bulb mimicking a membranous ventricular septal defect (VSD) with Eisenmenger reaction by transthoracic echocardiography. Aortic angiography showed a dilated aortic root and moderate aortic regurgitation. Right cardiac catheterization, on the other hand, exhibited normal pulmonary artery blood pressure and normal pulmonary resistance, whereas normal venous gas values were measured throughout the caval vein and the right atrium, excluding relevant left-right shunting. Further diagnostic workup by cardiac computed tomography angiography (CCTA) unambiguously illustrated the asymmetric geometry of the ectatic aortic cusp and root causing compression of the right heart and of the right ventricular (RV) outflow tract. After review of echocardiographic acquisitions, the blood flow detected between the left and right ventricles (mimicking VSD) was interpreted as turbulent inflow from the left ventricle into the ectatic right coronary cusp. Furthermore, elevated pulmonary artery blood pressure measured by echocardiography was attributed to "functional pulmonary stenosis" due to compression of the RV outflow tract by the aorta, as demonstrated by CCTA.